2011
DOI: 10.5251/ajsir.2011.2.2.136.143
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of sun and solar drying of peeled and unpeeled ginger

Abstract: Fresh ginger rhizomes were washed, sorted and cut into desired sizes using a knife. Some were peeled to remove the cork skin while others were left unpeeled with the cork skin. The samples were dried in a solar dryer and the open air for two weeks and designated; solar peeled and unpeeled, and open-air peeled and unpeeled Some physico-chemical and organoleptic analyses were carried out on the samples before, during and after drying. The results obtained showed that open-air dried products retained its colour a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 6 publications
6
29
0
1
Order By: Relevance
“…Contamination may also be introduced by food handlers or drying platforms with low sanitary standards. This was confirmed by Karabulut and others () and Eze and Agbo () who found an increase in natural microbiota after sun drying. They concluded that higher levels of microbial contamination were inevitable during traditional sun drying.…”
Section: Inactivation Of Microorganisms During Drying Processessupporting
confidence: 73%
“…Contamination may also be introduced by food handlers or drying platforms with low sanitary standards. This was confirmed by Karabulut and others () and Eze and Agbo () who found an increase in natural microbiota after sun drying. They concluded that higher levels of microbial contamination were inevitable during traditional sun drying.…”
Section: Inactivation Of Microorganisms During Drying Processessupporting
confidence: 73%
“…Agricultural product drying has a vital role in the preservation and shelf life improvement of the product after harvesting (Eze & Agbo, 2011). In developing countries, sun-drying is a popular, effective, and economical method for drying of food and herbal products.…”
mentioning
confidence: 99%
“…Tingginya kandungan minyak atsiri yang terdapat pada kunyit dibandingkan dengan jahe dan salam membuat suhu rektal ayam broiler lebih optimal karena dengan adanya minyak atsiri membuat nafsu makan broiler meningkat sehingga nutrisi yang masuk kedalam tubuh jadi lebih bayak dan metabolism tubuhpun optimal. Setiap 100 gr kunyit mengandung 4,2 -14 % minyak atsiri (Simanjuntak, 2012), pada jahe 1-3% (Eze dan Agbo, 2011). Sedangkan pada salam mengandung 0,05% minyak atsiri (Mohd, 2009(Mohd, dalam azis et al, 2014.…”
Section: Suhu Rektalunclassified